Therapeutic recombinant murine activated protein C attenuates pulmonary coagulopathy and improves survival in murine pneumococcal pneumonia - Schouten, Marcel; van 't Veer, Cornelis; van den Boogaard, Florry E; Gerlitz, Bruce; Grinnell, Brian W; Roelofs, Joris J T H; Levi, Marcel; van der Poll, Tom (The Journal of infectious diseases, 2010)
Recombinant human activated protein C (APC) improves survival of patients with severe sepsis; this beneficial effect is especially apparent in patients with pneumococcal pneumonia. The aim of this study was to determine the effect of APC treatment initiated after induction of pneumococcal pneumonia on pulmonary coagulation, inflammation, and survival, with or without concurrent antibiotic therapy. Mice were infected intranasally with viable Streptococcus pneumoniae and were treated intraperitoneally after 24 h of infection with vehicle, recombinant mouse (rm) APC (125 μg), ceftriaxone (500 μg), or rm-APC plus ceftriaxone. Treatment with rm-APC or vehicle was repeated every 8 h for a maximum of 96 h. Animals were either killed 48 h after infection or were monitored in a survival study (with an extra dose of ceftriaxone given after 72 h). Rm-APC treatment inhibited pulmonary activation of coagulation, as reflected by lower levels of thrombin-antithrombin complexes and D-dimer. Rm-APC did not affect the pulmonary levels of 55 inflammatory mediators in the context of antibiotic therapy. Rm-APC added to ceftriaxone markedly improved survival, compared with ceftriaxone treatment alone. Rm-APC inhibits pulmonary activation of coagulation and, when added to antibiotic therapy, improves survival in murine pneumococcal pneumonia.